THU0756-HPR Predictors of fear of movement in patients with rheumatoid arthritis. (15th June 2017) - Kinikli, GI; Guney, H; Karahan, S; Ates, A; Turgay, M; Kinikli, G
Abstract : Background: Rheumatoid arthritis (RA) is a systemic chronic autoimmune inflammatory disease characterized by synovial joint inflammation that results in functional limitations accompanied by social and psychological outcomes. Objectives: The aim of this study was to investigate the association between fear of movement and age, upper and lower extremity functions and functional disability in patients with Rheumatoid Arthritis (RA). Methods: A total of 88 patients with RA participated to the study. Disease activity was assessed using the Disease Activity Score in 28 joints (DAS28). Functional disability was assessed using the Health Assessment Questionnaire-Disability Index (HAQ-DI). The Disabilities of the Arm, Shoulder and Hand Score (QuickDASH) was used to assess the upper extremity function. The Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC) was used to assess the lower extremity function. The Tampa Scale for Kinesiophobia (TSK) was used to assess pain-related fear of movement. The multiple stepwise linear regression model with R-square (R 2 ) was used to compare across the models and explain the total variance. Results: Eight independent variables namely, age (r=0.215; p=0.044), QuickDASH (r=0.504; p<0.001), HAQ-DI (r=0.315; p=0.003), WOMAC Pain (r=0.512; p<0.001), WOMAC Stiffness (r=0.419; p<0.001), WOMAC Function (r=0.398; p<0.001), WOMAC Total (r=0.429; p<0.001), WOMAC range (r=0.419; p<0.001), demonstrated significant correlations with TSK. There were correlations between two independent variables (QuickDASH, p=0.013; WOMAC Pain, p=0.034) and TSK (R 2 =0.293). Conclusions: Health professionals should keep in mind that fear of movement were likely to cause poorer upper extremity functional disability and lower extremity pain levels in spite of varied drug therapies in patients with RA. References: Wan, S. W., He, H.-G., Mak, A., Lahiri, M., Luo, N., Cheung, P. P., & Wang, W. (2016). Health-related quality of life and its predictors among patients with rheumatoid arthritis. Applied Nursing Research, 30, 176–183. Doury-Panchout, F., Metivier, J., & Fouquet, B. (2015). Kinesiophobia negatively influences recovery of joint function following total knee arthroplasty. European journal of physical and rehabilitation medicine, 51(2), 155–161. Disclosure of Interest: None declared